2019
DOI: 10.1371/journal.pone.0218444
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib interferes with cell cycle, ABC transporters and JAK-STAT signaling pathway in CD34+/lin- cells of patients with chronic phase chronic myeloid leukemia after 12 months of treatment

Abstract: Chronic myeloid leukemia (CML) is characterized by the constitutive tyrosine kinase activity of the oncoprotein BCR-ABL1 in myeloid progenitor cells that activates multiple signal transduction pathways leading to the leukemic phenotype. The tyrosine-kinase inhibitor (TKI) nilotinib inhibits the tyrosine kinase activity of BCR-ABL1 in CML patients. Despite the success of nilotinib treatment in patients with chronic-phase (CP) CML, a population of Philadelphia-positive (Ph+) quiescent stem cells escapes the drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Afterward, we performed GEP analysis of BM CD34+/lin− cells of 79 pts at diagnosis vs the same pts after 12 months of treatment vs 10 CTRLs. We demonstrated the over‐expression of genes involved in the cell cycle and mitosis (n = 34), genes belonging to the JAK‐STAT signaling pathway ( SOS1, PIK3CA, IL7, JAK2, STAM, and PTPN11 ), and the ABC transporter gene ABCD3 at diagnosis vs 12 months of Nilotinib vs CRTLs 28 …”
Section: Resultsmentioning
confidence: 99%
“…Afterward, we performed GEP analysis of BM CD34+/lin− cells of 79 pts at diagnosis vs the same pts after 12 months of treatment vs 10 CTRLs. We demonstrated the over‐expression of genes involved in the cell cycle and mitosis (n = 34), genes belonging to the JAK‐STAT signaling pathway ( SOS1, PIK3CA, IL7, JAK2, STAM, and PTPN11 ), and the ABC transporter gene ABCD3 at diagnosis vs 12 months of Nilotinib vs CRTLs 28 …”
Section: Resultsmentioning
confidence: 99%
“…At present, there are only a few studies on the role and underlying mechanism of ABCD3 in tumors, such as prostate tumor (16), ovarian cancer (15,17), colon cancer (14), chronic myeloid leukemia (25), melanoma (26) and retinoblastoma (27). However, the aforementioned studies only investigated the difference of ABCD3 mRNA or protein expression in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study by Trojani et al ( 51 ) demonstrated that long-term use of second-generation TKI (nilotinib) in CML patients can induce the upregulation of ABC transporters (ABCC4, ABCC5, ABCD3) in bone marrow CD34 + /lin − cells. Another independent study by Mehrvar et al ( 52 ) demonstrated the changes in expression pattern of ABCC transporters in peripheral blood leukocytes of patients with acute lymphoblastic leukemia (ALL) recurrence.…”
Section: Discussionmentioning
confidence: 99%